2021
DOI: 10.1097/rhu.0000000000001592
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Corneal Nerve Density and Symptoms of Small Fiber Neuropathy in Patients With Fibromyalgia: The Confounding Role of Severe Anxiety or Depression

Abstract: Objective: A consistent line of investigation proposes fibromyalgia as a dysautonomia-associated neuropathic pain syndrome. Comorbid anxiety or depression amplifies fibromyalgia symptoms. The recent recognition of small fiber neuropathy in fibromyalgia patients supports the neuropathic nature of the illness. Corneal confocal microscopy accurately identifies small nerve fiber pathology. The newly developed Small-Fiber Symptom Survey captures the spectrum of small fiber neuropathy symptoms. We aimed to correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
(31 reference statements)
1
14
0
1
Order By: Relevance
“…In the second, Ramìrez et al (40) found correlations between corneal denervation and SFN and the symptoms of dysautonomia in female FM patients unaffected by severe anxiety or depression, whereas their profoundly anxious or depressed counterparts showed no clinical-pathological correlations even though their symptoms were more intense, thus confirming that severe psychiatric symptoms play a confounding role.…”
Section: Small Fiber Neuropathy (Sfn)mentioning
confidence: 98%
See 1 more Smart Citation
“…In the second, Ramìrez et al (40) found correlations between corneal denervation and SFN and the symptoms of dysautonomia in female FM patients unaffected by severe anxiety or depression, whereas their profoundly anxious or depressed counterparts showed no clinical-pathological correlations even though their symptoms were more intense, thus confirming that severe psychiatric symptoms play a confounding role.…”
Section: Small Fiber Neuropathy (Sfn)mentioning
confidence: 98%
“…• Neurophysiologically, the pattern of brain activation is not due to functional or structural alterations in the areas involved in acute pain, thus chronic pain is not just "longer-lasting pain" (36,37). • The Pain Detect Questionnaire (PDQ), the Douleur Neuropathique 4 questions (DN4), sural nerve crosssectional area and corneal denervation can be used to non-invasively diagnose SFN (39,40).…”
Section: Take Home Messagesmentioning
confidence: 99%
“…The eye cornea is the most pain-sensitive part of the body owing to the extremely dense small fiber innervation. This feature makes the cornea the ideal site to study small nerve fiber pathology [8].…”
Section: Dorsal Root Ganglia Unique Anatomymentioning
confidence: 99%
“…Small fiber neuropathy is a denervating disease. Fibromyalgia patients without marked anxiety or depression display strong correlation between corneal denervation and small fiber neuropathy symptom burden [8]. A tentative explanation for the peripheral denervation seen in small fiber neuropathy is DRG nuclear degeneration.…”
Section: Dorsal Root Ganglia Immune Competencementioning
confidence: 99%
“…Another proposed underlying pathogenic factor for SS development is the presence of small fiber neuropathy 5 . The association between increased anxiety levels and small fiber neuropathy is well established in fibromyalgia, diabetic neuropathy, and burning mouth syndrome 6–10 . The role of depression and psychiatric factors in the development of sensitive skin has also been shown in the previous studies 11–13 .…”
Section: Introductionmentioning
confidence: 77%